Intellectual Capital in the Period of Industry 4.0: A Research on the Information Sector - İlknur Ergün; İrem Özcan (Muhasebe Enstitüsü Dergisi)
This era’s digital transformation has significantly increased the number and effectiveness of enterprises using information technologies (IT) to operate. The difference between an IT enterprise’s book value and market value is explained as intellectual capital. The study aims to determine whether the intellectual capital is higher for the enterprises traded in the Borsa İstanbul (BIST) stock exchange’s information sector and calculate the amount. Considering that the Industry 4.0 roadmap was devised in Turkey in 2018 and the awareness of enterprises regarding this issue has increased, the financial statement data of enterprises in 2018, 2019 and 2020 have been analyzed using the calculated intangible value method. Of the 18 enterprises, 3 did not meet the analysis requirements and were excluded, so the intellectual capital value was for 15 enterprises. When the results were compared with those of previous studies, the value of intellectual capital in the IT sector increased significantly. Thus, it was concluded that in this change, the increase in the contribution of intellectual capital in Industry 4.0 applications are effective.